ON THE TITLE AND LEXICAL FEATURES OF THE WINTER OLYMPICS NEWS REPORT IN CHINA DAILY - Yuan, Xiaowei (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
With the successful hosting of the 2022 Winter Olympics, people all over the world have turned more attention to Chinese winter sports. China Daily is major media to know the news about it. This article made an analysis of the title and lexical features of the Winter Olympics through the news from China Daily.